Our Bearings : Poems - McGlennen, Molly (Sun tracks, 2020)
"Our Bearings is a collection of narrative poems about Anishinaabe life in modern Minneapolis. The four elements - earth, air, water, and fire - separate the poems into four distinct sections, throughout which McGlennen weaves together a beautifully layered portrait of a city and family from the perspective of an Anishinaabe woman who lives in, and sees, another Minneapolis. This is a Minneapolis burdened by its ugly history and the ever-present shadow of an earlier, more Indigenous landscape, but is also one that lives on as a place, both real and imagined, that is deeply home. The poems are interested in specific landscapes and people, and there is a strong, almost speculative sense of what Minneapolis might have looked like without colonization. Throughout the collection McGlennen skillfully charts an Indigenous mapping of spaces as she shows us that we are neither the first, nor will we be the last, to walk these paths around us"--